The effect of ACTH4-10Pro8-Gly9-Pro10 on neurotrophin-3 expression in Sprague Dawley rat on acute spinal cord injury - Made Gemma Daniswara Maliawan, Made
Abstract Background: Neurotrophic factors such as NT-3 play an important role in spinal cord regeneration, contributing to spinal cord regeneration assisting functional improvement in SCI. ACTH4-10Pro8-Gly9-Pro10, an analog of the N-terminal fragment (4-10) adrenocorticotropic hormone, is one of the neuroprotective compounds that can increase NT-3 levels in brain ischemia. Therefore, we conducted a study with experimental animals to determine the effect of NT-3 expression on ACTH4-10Pro8-Gly9-Pro10 administration in acute compression SCI.